Bone formation and mineralization around the implant in osteoporotic animal models enhanced by mesenchymal stem cells - Hendrijantini, Nike; Kuntjoro, Mefina; Agustono, Bambang; Ari, Muhammad Dimas Aditya; Kurdi, Abil; Mundiratri, Karina; Prasetyo, Eric Priyo; Hong, Guang (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Poor bone quality, sometimes caused by osteoporosis, can lead to dental implant failure. Human umbilical cord mesenchymal stem cells (hUCMSCs) can differentiate into osteoblasts and offer an alternative therapy for poor bone conditions. Purpose: This study aims to evaluate the effect of hUCMSCs induction on the extent of osseointegration by the new bone formation area of dental implants in osteoporotic animal models. Methods: The samples were divided into two groups, i.e., control and induced hUCMSCs groups at different times. An ovariectomy was performed to assess the osteoporosis condition. The control group was injected using gelatin, and the treatment group was administered hUCMSCs. Terminations were conducted at 2 and 4 weeks, respectively. The collected samples were then subjected to histological examination to analyze new bone formation and its proportion. In addition, alkaline phosphatase staining was also performed to evaluate the mineralization area. The data was analyzed using the one-way analysis of variance (ANOVA). Results: Both for new bone formation area as well as the proportion of new bone, it was observed that the best results were in the group with induction of hUCMSCs at 2 weeks. Alkaline phosphatase staining also confirmed that the highest mineralization was observed in the same group. Conclusion: hUCMSCs induced new bone formation in the implant placement in osteoporotic animal models.